The high-power helicon program at DIII-D: gearing up for first experiments. (5th October 2021) - Van Compernolle, B.; Brookman, M.W.; Moeller, C.P.; Pinsker, R.I.; Garofalo, A.M.; O'Neill, R.; Geng, D.; Nagy, A.; Squire, J.P.; Schultz, K.; Pawley, C.; Ponce, D.; et al.
Abstract: Helicon current drive (CD), also called fast wave CD in the lower hybrid range of frequencies, has long been regarded as a promising CD tool for reactor grade plasmas. A newly installed MW-level system at DIII-D will be the first test of this technology in reactor-relevant plasmas, in the sense that full single-pass absorption is expected. A 30-module traveling wave antenna has been installed and optimized in-vessel in early 2020. The linear electromagnetic characteristics of the unloaded module array have been extensively tested both on the bench and in the vessel at instrumentation power levels. Excellent performance has been achieved, ∼2% reflected power and ∼1.5% dissipated power per module in air, in a 10 MHz band around 476 MHz. Stripline feeds on both ends of the antenna allow either co or counter CD. The installation of a 1.2 MW klystron and associated high-power electronics was completed in Fall 2020. Commissioning of the antenna is ongoing. An important goal of this experiment is to validate the helicon CD physics basis using an extensive set of new and upgraded diagnostics.